Spinal analgesic interaction between non-steroidal anti-inflammatory drugs and N-methyl-D-aspartate receptor systems : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Veterinary Science, Institute of Veterinary, Animal and Biomedical Sciences, Massey University, Palmerston North, New Zealand - Lizarraga-Madrigal, Ignacio (Massey University, 2006)
Activation of spinal N-methyl-D-aspartate (NMDA) receptors stimulates cyclooxygenase and nitric oxide pathways. Compounds that block the activity of these NMDA receptor systems reduce pain hypersensitivity. However, their usefulness is limited by the side effects they produce. One way of reducing side effects is by combining drugs that produce the same overt effect by different mechanisms, which hopefully increase the net effect. In these series of studies, drugs that interact with NMDA receptor systems and their combinations were screened in vitro to identify spinal antinociceptive synergistic combinations that could be assessed in vivo. Based on developmental changes in thresholds, conduction velocities and blocking actions of the local anaesthetic lignocaine in neonatal rat L4/L5 dorsal root potentials, it was decided to use spinal cord in vitro preparation from 5- to 7-day-old rat pups. In single drug studies, the NMDA receptor channel blocker ketamine (1-50 µM) and the non-steroidal anti-inflammatory drug (NSAID) ketoprofen (200-600 µM), but not the NSAID salicylate (1000 µM) and the nitric oxide synthase inhibitor Nω-nitro-L-arginine methyl ester (L-NAME; 1-100 µM), reduced spinal NMDA receptor-mediated transmission. Ketamine also depressed non-NMDA receptor-mediated transmission. Using isobolographic and composite additive line analyses, fixed-ratio combinations of ketamine and ketoprofen, ketamine and L-NAME, and ketopofen and L-NAME synergistically depressed NMDA receptor-mediated transmission. The two former combinations had a subadditive effect on non-NMDA receptor-mediated transmission, and the latter had no significant effect. These studies identified that all combinations synergistically reduced both nociceptive transmission and potential side effects. In free-moving sheep implanted with indwelling cervical intrathecal catheters, 100 µ1 subdural administration of ketamine (25-400 µM) and ketoprofen (200-3200 µM) alone and in a fixed-ratio combination (873.95-3350.78 µM, 0.045:0.955) did not raise nociceptive thresholds as assessed by mechanical stimulation of one foreleg. Subdural administration of NMDA (2 mM) decreased mechanical nociceptive thresholds, and this was prevented by the highest concentrations of ketamine and ketoprofen alone and in combination. These findings demonstrated that NMDA receptor channel blockers and NSAIDs alone or in combination had no direct hypoalgesic effects when given onto the spinal cord of sheep, but they prevented NMDA-induced pain hypersensitivity. Simultaneous blockade of NMDA receptor systems could have important clinical implications.
Keywords: Spinal anaesthesia; Nonsteriodal anti-inflammatory agents; Veterinary chemotherapy; Fields of Research::300000 Agricultural, Veterinary and Environmental Sciences::300500 Veterinary Medicine::300502 Anaesthesiology and intensive care